Atazanavir/ritonavir monotherapy: 96 week efficacy, safety and bone mineral density from the MODAt randomized trial. (5th March 2016) - Galli, Laura; Spagnuolo, Vincenzo; Bigoloni, Alba; D'Arminio Monforte, Antonella; Montella, Francesco; Antinori, Andrea; Di Biagio, Antonio; Rusconi, Stefano; Guaraldi, Giovanni; Di Giambenedetto, Simona; Borderi, Marco; Gibellini, Davide; et al.
Abstract: Objectives: To report the 96 week results on efficacy, safety and bone mineral density (BMD) in subjects with HIV-1 that were virologically suppressed and treated with atazanavir/ritonavir monotherapy versus atazanavir/ritonavir triple therapy. Methods: MODAt is a prospective, multicentre, open-label, non-inferiority, randomized, 96 week trial (NCT01511809) comparing efficacy of atazanavir/ritonavir monotherapy versus atazanavir/ritonavir triple therapy. Treatment success was defined as no occurrence of confirmed viral rebound (two consecutive HIV-RNA >50 copies/mL) or discontinuation for any cause of the ongoing regimen. Results: The 96 week treatment success was 64% in the atazanavir/ritonavir monotherapy arm and 63% in the triple-therapy arm (difference 1.3%, 95% CI: −17.5 to 20.1). In the atazanavir/ritonavir monotherapy arm, no PI- or NRTI-associated resistance mutations were observed at virological failure and all patients re-suppressed after re-intensification. In the monotherapy arm, treatment failure was more frequent in patients coinfected with hepatitis C virus [64% versus 28% (difference 35.4%, 95% CI: 3.7–67.2)]. Drug-related adverse events leading to discontinuation were 3 (6%) in the atazanavir/ritonavir monotherapy arm and 11 (21.5%) in the triple-therapy arm ( P  = 0.041). The 96 week adjusted mean percentage change in total proximal femur (not at lumbar spine) BMD was +1.16% and −1.64% in the atazanavir/ritonavir monotherapy arm and the triple-therapy arm, respectively ( P  = 0.012). Conclusions: The 96 week analyses suggested that long-term efficacy of atazanavir/ritonavir monotherapy was inferior as compared with atazanavir/ritonavir triple therapy, particularly when administered in subjects coinfected with hepatitis C virus. In the atazanavir/ritonavir monotherapy arm, reintroduction of nucleosides, as needed, was always effective with no new resistance mutation; monotherapy was also associated with a lower incidence of adverse events and improvement in femur BMD.